Induction of T helper 17 cell response by interleukin-7 in patients with primary cutaneous melanoma. Issue 4 (August 2021) - He, Hongxia; Qiao, Binjun; Guo, Shuping; Cui, Hongzhou; Li, Ning; Liu, Hongye; Qin, Junxia; He, Jinghong; Yang, Xiaofeng; Xue, Wenli; Wang, Yanzhen
Abstract : Interleukin (IL)-7 plays a vital role in proliferation and activation of T cells, however, its signaling through CD127 is impaired in T cells in cancers and chronic infections. The mechanisms underlying T helper 17 (Th17) cell responses by IL-7 in melanoma remain not fully understood. The aim of this study was to assess the effect of IL-7 signaling on Th17 responses in patients with primary cutaneous melanoma. Healthy and primary cutaneous melanoma donors were selected for this study of Th17 cell function. IL-17 + CD4 + Th17 cells and CD127 expression on Th17 cells were determined by flow cytometry. Cytokine level was measured by ELISA. Peripheral and tissue-infiltrating CD4 + T cells were isolated using magnetic beads, and then stimulated with IL-7 and/or signal transducer and activator of transcription 5 inhibitor. Activated signaling molecules were analyzed by flow cytometry. Peripheral and tumor-infiltrating Th17 cells percentage was decreased, while peripheral IL-7 level was also reduced in melanoma patients. There was no significant difference of CD127 expression on Th17 cells between melanoma patients and controls. Antiapoptotic protein Bcl-2 was downregulated, whereas proapoptotic protein-activated caspase-3 was upregulated in peripheral and tissue-infiltrating Th17 cells in melanoma patients. Higher concentration of IL-7 (10 ng/mL), but not lower IL-7 concentration (1 ng/mL), promoted Bcl-2 expression and decreased caspase-3 expression in Th17 cells in melanoma patients. Inhibition of signal transducer and activator of transcription 5 resulted in the downregulation of Bcl-2 while upregulation of caspase-3 in Th17 cells. The present data suggested that reduced IL-7 responsiveness might be insufficient for Th17 activation in patients with primary cutaneous melanoma.